Autologous Microfragmented Adipose Tissue Reduces the Catabolic and Fibrosis Response in an In Vitro Model of Tendon Cell Inflammation - Marco Viganò; Gaia Lugano; Carlotta Perucca Orfei; Alessandra Menon; Enrico Ragni; Alessandra Colombini; Paola De Luca; Pietro Randelli; Laura de Girolamo (Hindawi Limited, 2019)
Background. Mesenchymal stem cells (MSCs) emerged as a promising therapy for tendon pathologies. Microfragmented adipose tissue (μFAT) represents a convenient autologous product for the application of MSC-based therapies in the clinical setting. In the present study, the ability of μFAT to counteract inflammatory processes induced by IL-1β on human tendon cells (TCs) was evaluated. Methods. Cell viability and proliferation were evaluated after 48 hours of transwell coculture of TCs and autologous μFAT in the presence or absence of IL-1β. Gene expression of scleraxis, collagen type I and type III, metalloproteinases-1 and -3, and cyclooxygenase-2 was evaluated by real-time RT-PCR. The content of VEGF, IL-1Ra, TNFα, and IL-6 was evaluated by ELISA. Results. IL-1β-treated TCs showed augmented collagen type III, metalloproteases, and cyclooxygenase-2 expression. μFAT was able to reduce the expression of collagen type III and metalloproteases-1 in a significant manner, and at the same time, it enhanced the production of VEGF, IL-1Ra, and IL-6. Conclusions. In this in vitro model of tendon cell inflammation, the paracrine action of μFAT, exerted by anti-inflammatory molecules and growth factors, was able to inhibit the expression of fibrosis and catabolic markers. Then, these results suggest that the application of μFAT may represent an effective conservative or adjuvant therapy for the treatment of tendon disorders.